Effects of Driving Torques on Direct Screw Withdrawal Resistance in OSB - Tor, Önder; Demirel, Samet; Hu, Lingling; Zhang, Jilei (Kastamonu University, 2016)
This study was performed to evaluate effects of driving torques on direct screw withdrawal resistance (DSWR) in wood-based composites. Pilot hole diameters (1.6, 2, 2.4 mm), embedded screw orientations (edge-, end- and face-) and torque levels, that were obtained from the typical driving torque curve among two main driving torques, were selected to test on screw withdrawal resistance. The results of the study showed that the pilot hole diameters were needed to be chosen carefully related to the grain orientation. The screw withdrawal resistance in face-grain orientation had the highest DSWR than the ones in edge- and end- grain orientations. Based on the torque levels selected that the DSWR was lower at the torque level closer to the stripping torque levels in OSB.
Keywords: Çekme direnci; Vidalama torkları; Kılavuz delik çapı; OSB; Withdrawal resistance; Driving torque; Pilot hole diameter; Grain orientation; OSB